1970
DOI: 10.1901/jeab.1970.13-267
|View full text |Cite
|
Sign up to set email alerts
|

A PRELIMINARY ANALYSIS OF THE DYNAMICS OF THE PECKING RESPONSE IN PIGEONS1

Abstract: The pecking response of pigeons is usually measured by a transducer that senses the preseCice or absence of a response. Typically, the response force as a function of time has not beet accurately measuredl. Data were collected using a transducer specially designed to recor(l thc waveform of the pecking respolIse in pigeons. Each responsc on the target surface of the tranlsducer was reinforced antd followe(l by a blackout. The response was stored on an oscilloscope screen and the peak force atitd tluration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1971
1971
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…The technology for equivalent approaches in the laboratory is available (e.g., Weiss, 1970b;Rilling, Kramer, and Askew, 1970) and ought to be applied more vigorously.…”
Section: Components Of Fr Performancementioning
confidence: 99%
“…The technology for equivalent approaches in the laboratory is available (e.g., Weiss, 1970b;Rilling, Kramer, and Askew, 1970) and ought to be applied more vigorously.…”
Section: Components Of Fr Performancementioning
confidence: 99%
“…For the interface (controller) hardware provided with the Duratouch screen, a contact duration of at least 13 ms was required to generate a readout of the touch location in x and y coordinates. Unpublished observations from our laboratory and some published reports (Rilling, Kramer, & Askew, 1970;Schwartz & Williams, 1972;Whipple & Fantino, 1980) suggested that a substantial proportion of conditioned pecking-response contacts may be less than 10 ms in duration. For this reason, we replaced the commercial controller with a circuit that samples the x, y outputs of the touch screen at rates sufficient to detect the location of a peck contact with a duration of 2 ms or greater.…”
Section: Transducersmentioning
confidence: 81%
“…In previous studies of pecking response duration, contact duration was measured either as the duration of displacement of a standard pecking-response key (e.g., Schwartz & Williams, 1972;Whipple & Fantino, 1980) or by using force transducers, which provide a voltage analogue representation of the force-time function (LaMon & Zeigler, 1984;Rilling et al, 1970). The waveforms and the distributions of touch screen contact durations shown in Figure 4 reflect the direct measurement of contact duration, independent of pecking force.…”
Section: Discussionmentioning
confidence: 95%
“…The time series were then filtered to find pecks. Our definition of pecks arose out of our pilot work and reports in the literature on the duration and forcefulness of pigeons’ pecks (e.g., Rilling et al, 1970). Eventually, our definition identified pecks as any event that exceeded 80 g and returned to subthreshold forces (< 10 g) within 30 ms.…”
Section: Methodsmentioning
confidence: 99%